1979
DOI: 10.1182/blood.v54.4.872.872
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of normal and sickle erythrocytes to endothelial monolayer cultures

Abstract: Experiments were carried out to test the hypothesis that the differences between the surfaces of erythrocytes from normal and sickle cell patients are reflected in the degree of attachment to the capillary lining. An assay was used that measured the number of 51Cr- labeled erythrocytes (normal or sickle) attaching to a monolayer of endothelium cultured from calf aortas. Under these conditions, erythrocytes from sickle cell patients adhered better to the endothelium than did those from normal patients. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(41 citation statements)
references
References 12 publications
2
39
0
Order By: Relevance
“…Red blood cells from patients with sickle cell disease (SS RBC) have abnormally strong adhesive interactions with vessel endothelium and components of the subendothelial matrix. The presence of various cytokines in sickle cell patients, 25‐31 as well as contact of normal RBCs with endothelial cells, causes retraction and/or detachment of endothelial cells 32 and thus may lead to exposure of subendothelial matrix components to circulating cells 33‐36 . SS RBCs adhere abnormally well to several components of the subendothelial matrix, but the strongest interaction is with the heterotrimeric protein laminin 37 .…”
Section: Functional Roles Of B‐cam/lumentioning
confidence: 99%
See 1 more Smart Citation
“…Red blood cells from patients with sickle cell disease (SS RBC) have abnormally strong adhesive interactions with vessel endothelium and components of the subendothelial matrix. The presence of various cytokines in sickle cell patients, 25‐31 as well as contact of normal RBCs with endothelial cells, causes retraction and/or detachment of endothelial cells 32 and thus may lead to exposure of subendothelial matrix components to circulating cells 33‐36 . SS RBCs adhere abnormally well to several components of the subendothelial matrix, but the strongest interaction is with the heterotrimeric protein laminin 37 .…”
Section: Functional Roles Of B‐cam/lumentioning
confidence: 99%
“…Many studies have shown that SS RBCs adhere more avidly than normal RBCs to cultured endothelial cells, 33,35 , 53 and the increased level of circulating endothelial cells in sickle cell patients also suggests a possible SS RBC interaction with endothelial cells in vivo 36 . Endothelial integrin proteins may be important in the interaction of SS RBCs with endothelial cells, although the precise integrins and the characteristics of these interactions are still under investigation 54 .…”
Section: Functional Roles Of B‐cam/lumentioning
confidence: 99%
“…The polymerization of deoxygenated HbS results in the formation of rigid and fragile sickle red blood cells (RBCs) responsible for painful vascular occlusion and chronic anaemia, respectively. In addition, sickle RBCs have increased adhesiveness to white blood cells (Belcher et al , ; Frenette, ), platelets (Antonucci et al , ; Wun et al , ) and endothelial cells (Hoover et al , ; Hebbel et al , ), which may participate to the initiation of vaso‐occlusive like events.…”
mentioning
confidence: 99%
“…The reason SCD RBCs cause such damage in the microvasculature through vaso-occlusion and hemolytic anemia is the propensity of sickle (HbS) hemoglobin to polymerize under low oxygen tension [107]. This process changes the shape and rigidity of the RBC membrane as well as its adhesiveness [108].…”
Section: Erythrocyte-endothelium Interfacementioning
confidence: 99%